Performance of axially loaded tapered concrete-filled steel composite slender columns - Bahrami, Alireza; Wan Badaruzzaman, Wan Hamidon; Osman, Siti Aminah (Journal of Civil Engineering and Management, 2013)
This paper focuses on the performance of a special kind of tapered composite columns, namely tapered concrete-filled steel composite (TCFSC) slender columns, under axial loading. These efficient TCFSC columns are formed by the increase of the mid-height depth and width of straight concrete-filled steel composite (CFSC) slender columns, that is, by the enhancement of the tapered angle (from 0° to 2.75°) of the tapered composite columns from their top and bottom to their mid-height. To investigate the performance of the columns, finite element software LUSAS is employed to carry out the nonlinear analyses. Comparisons of the nonlinear finite element results with the existing experimental results uncover the reasonable accuracy of the proposed modelling. Nonlinear analyses are extensively performed and developed to study effects of different variables such as various tapered angles, steel wall thicknesses, concrete compressive strengths, and steel yield stresses on the performance of the columns. It is concluded that increasing each of these variables considerably enhances the ultimate axial load capacity. Also, enhancement of the tapered angle and/or steel wall thickness significantly improves the ductility. Moreover, confinement effect of the steel wall on the performance of the columns is evaluated. Failure modes of the columns are also presented.